Nature of magnetization and lateral spin–orbit interaction in gated semiconductor nanowires. (2nd May 2018) - Karlsson, H; Yakimenko, I I; Berggren, K-F
Abstract: Semiconductor nanowires are interesting candidates for realization of spintronics devices. In this paper we study electronic states and effects of lateral spin–orbit coupling (LSOC) in a one-dimensional asymmetrically biased nanowire using the Hartree–Fock method with Dirac interaction. We have shown that spin polarization can be triggered by LSOC at finite source-drain bias, as a result of numerical noise representing a random magnetic field due to wiring or a random background magnetic field by Earth magnetic field, for instance. The electrons spontaneously arrange into spin rows in the wire due to electron interactions leading to a finite spin polarization. The direction of polarization is, however, random at zero source-drain bias. We have found that LSOC has an effect on orientation of spin rows only in the case when source-drain bias is applied.